A lithium ion battery graphite negative electrode regeneration method and regenerated graphite

Through a lithium-ion battery graphite negative electrode regeneration method including peeling, impurity removal, shear mixing and high-temperature carbonization steps, the problem of structural collapse of graphite negative electrode materials during cyclic charging and discharging is solved, efficient regenerated graphite performance is improved, and the cycle life of the battery is extended.

CN118811809BActive Publication Date: 2025-03-18HUBEI JINGHUAN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411107556.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-03-18
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

During the cycle charging and discharging process of lithium-ion batteries, the structural expansion and contraction of graphite negative electrode materials lead to structural collapse, affecting their recovery and regeneration performance, resulting in a decrease in the battery cycle stability and capacity retention rate.

Method used

A method of regeneration of graphite anode of lithium-ion batteries is adopted, including peeling, decomposition, shear mixing and high-temperature carbonization steps of graphite anode. The adhesive and conductive agent are removed by peeling off and crushing the graphite negative electrode active material coating, impurities are removed and the adhesive is interrupted, combined with heat treatment and ultrasonic pickling. Then, polytetrafluoroethylene resin and nanoboehmite were added, and the polytetrafluoroethylene resin was fibrated by shear mixing to form a fibrotic structure to bond the graphite material, and finally high-temperature carbonization was carried out to obtain regenerated graphite.

Benefits of technology

The graphite fine powder with structure collapse is effectively controlled, the circulation performance and capacity retention rate of recycled graphite is improved, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary battery materials. More specifically, it relates to a method for regenerating a graphite negative electrode of a lithium ion battery and regenerated graphite. The specific regeneration steps of the present invention include: stripping of the graphite negative electrode: stripping the graphite negative electrode active material coating and the negative electrode current collector, and then crushing the graphite negative electrode active material coating to obtain a crushed material; impurity removal: heat treating the crushed material in an air atmosphere, and then ultrasonic pickling to obtain a de-impurity material; shear mixing: mixing the de-impurity material and polytetrafluoroethylene resin in a mass ratio of (15-20): 1, and then adding flaky nano-boehmite of 1.5-2.5% of the mass of the de-impurity material, at a temperature of 40-50°C, continuously shear mixing for more than 3 hours to fiberize the polytetrafluoroethylene resin to obtain a precursor; high temperature carbonization: heating and carbonizing the precursor under inert gas protection, and sieving to obtain regenerated graphite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary battery materials, and more specifically, relates to a method for regenerating graphite negative electrodes of lithium-ion batteries and regenerated graphite. Background Art

[0002] During the battery charge and discharge cycle, the graphite negative electrode material is not only accompanied by the embedding and extraction of lithium ions, but also by the expansion and contraction of its physical structure, especially during rapid charge and discharge. Based on this, during the battery charge and discharge cycle, the graphite may undergo structural collapse, and this degradation will lead to a decrease in the battery's cycle stability and capacity retention rate. If a large amount of structurally collapsed graphite negative electrode material is recycled, then this part of the graphite material after structural collapse will be mixed into the recycled material. The introduction of this part of material will cause the product performance to become unstable and fall short of expectations. Summary of the invention

[0003] The technical problem to be solved by the present invention is the recycling and regeneration of graphite negative electrode materials. In the prior art, most people focus on how to remove the impurity elements therein. The inventors have found that during the battery charge and discharge cycle, the expansion and contraction of the negative electrode material volume can easily cause the collapse of the graphite structure, resulting in the inability to effectively guarantee the performance of the recycled negative electrode material. A method for regenerating graphite negative electrodes of lithium-ion batteries and regenerated graphite are provided.

[0004] The purpose of the present invention is to provide a method for regenerating a graphite negative electrode of a lithium ion battery.

[0005] Another object of the present invention is to provide a regenerated graphite.

[0006] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0007] A method for regenerating a graphite negative electrode of a lithium-ion battery, the specific regeneration steps comprising:

[0008] Stripping of graphite negative electrode:

[0009] The graphite negative electrode active material coating is peeled off from the negative electrode current collector, and then the graphite negative electrode active material coating is crushed to obtain a crushed material;

[0010] Remove impurities:

[0011] The crushed material is heat treated in an air atmosphere at a temperature below 400°C, and then ultrasonically pickled to obtain a decontaminated material;

[0012] Shear Mixing:

[0013] The impurity-removing material and the polytetrafluoroethylene resin are mixed in a mass ratio of (15-20):1, and then sheared and mixed to fiberize the polytetrafluoroethylene resin to obtain a precursor;

[0014] High temperature carbonization:

[0015] The precursor is heated and carbonized under the protection of inert gas, and then sieved to obtain regenerated graphite.

[0016] For the negative electrode plate of a lithium-ion battery, it is mainly composed of a negative electrode current collector and a negative electrode active material coating adhered to the surface of the negative electrode current collector. Generally speaking, the negative electrode current collector of the current mainstream graphite negative electrode is copper foil. In order to prevent copper from being mixed into the graphite material during subsequent processing, the negative electrode active material coating and the negative electrode current collector are first peeled off to prevent copper foil from being mixed in. In addition, for the negative electrode active material coating, its general composition includes graphite negative electrode active material, binder and conductive agent. The peeled negative electrode active material coating is crushed. During the crushing process, the binder can be broken, thereby refining the negative electrode active material coating. Then, in combination with heat treatment in an air atmosphere, the binder and conductive agent in the negative electrode active material coating can be oxidized. After removal, a certain amount of polytetrafluoroethylene resin is added, and the polytetrafluoroethylene resin is gradually fiberized in the shearing process by using the shearing process. The fiberized polytetrafluoroethylene resin can bond the graphite material, so that the fiberized shearing action can cause relative movement or slip between graphite and graphite, or between the surface and the inside of graphite, so that the fine powder with collapsed structure during the use or regeneration of graphite material can be fully exposed and separated, and then with the final heating carbonization process, the polytetrafluoroethylene is decomposed without residue and substantial impact on the performance of graphite; in this way, the collapsed graphite fine powder that is not desired to be mixed in the material can be effectively controlled, so that the gram capacity and cycle performance of the product can be effectively guaranteed;

[0017] The amount of polytetrafluoroethylene resin added needs to be strictly controlled. If the amount added is too little, it is difficult for it to fully adsorb or bond the graphite negative electrode material, so its effect is not sufficient; if it is added in excess, it is easy to remain, affecting the processing or performance of the product after regeneration, and it is also easy to increase costs.

[0018] Further, the shear mixing comprises:

[0019] The impurity-removing material and polytetrafluoroethylene resin are mixed in a mass ratio of (15-20):1, and then continuously shear-mixed for more than 3 hours at a temperature of 40-50°C to fiberize the polytetrafluoroethylene resin to obtain a precursor.

[0020] By regulating the appropriate processing temperature and time, a reasonable processing temperature is ensured to ensure that polytetrafluoroethylene is fully fiberized during the processing, while at the same time, its performance will not change due to excessively high temperature, thereby affecting the pulling force of fiberization on graphite.

[0021] Further, the shear mixing also includes:

[0022] The impurity-removing material and polytetrafluoroethylene resin are mixed in a mass ratio of (15-20):1, and then 1.5-2.5% of the mass of the impurity-removing material is added with flaky nano-boehmite, and the mixture is continuously sheared and mixed for more than 3 hours at a temperature of 40-50° C. to fiberize the polytetrafluoroethylene resin to obtain a precursor.

[0023] Furthermore, the specific regeneration step also includes:

[0024] Stripping of graphite negative electrode:

[0025] The graphite negative electrode active material coating is peeled off from the negative electrode current collector, and then the graphite negative electrode active material coating is crushed to obtain a crushed material;

[0026] Remove impurities:

[0027] The crushed material is heat treated in an air atmosphere at a temperature below 400°C, and then ultrasonically pickled to obtain a decontaminated material;

[0028] Shear Mixing:

[0029] The impurity-removing material and polytetrafluoroethylene resin are mixed in a mass ratio of (15-20):1, and then 1.5-2.5% of the mass of the impurity-removing material is added with flaky nano-boehmite, and the mixture is continuously sheared and mixed for more than 3 hours at a temperature of 40-50° C. to fiberize the polytetrafluoroethylene resin to obtain a precursor;

[0030] High temperature carbonization:

[0031] The precursor is heated and carbonized under the protection of inert gas, and then discharged after cooling, and then acid-washed and dried to obtain regenerated graphite.

[0032] Furthermore, the impurity removal also includes:

[0033] The crushed material is heat-treated in an air atmosphere to remove a binder and a conductive agent, and then ground and sieved to obtain a de-impurity material with a D50 of 12-20 μm;

[0034] Furthermore, the D50 of the nano-boehmite is 150-180 nm.

[0035] The inventors have found that if a certain amount of nano-sized boehmite is added to the system, it can cooperate with polytetrafluoroethylene to achieve a better effect on the separation of collapsed fine powders during the regeneration of graphite materials. Specifically, nano-scale flake boehmite is easily embedded in the layered graphite material under the action of processing shear force, and then with the help of the pulling force of the molecular chain of the fiberized polytetrafluoroethylene resin, the collapsed structure on the graphite surface can be separated. Due to its appropriate hardness, boehmite will not have a bad effect on the structure of the graphite material.

[0036] Furthermore, for the crushed materials of the above specifications, selecting boehmite with a suitable particle size can obtain a more uniform and sufficient treatment effect.

[0037] Further, the high temperature carbonization includes:

[0038] The precursor is heated to 580-600°C at a rate of 0.3-0.5°C / min under inert gas protection, carbonized for 3-6 hours, cooled to room temperature with the furnace, and discharged to obtain regenerated graphite.

[0039] A regenerated graphite is prepared by the above-mentioned lithium ion battery graphite negative electrode regeneration method. DETAILED DESCRIPTION

[0040] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0041] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0042] Example 1

[0043] Stripping of graphite negative electrode:

[0044] Disassemble the lithium-ion battery, separate and remove the positive electrode sheet and the separator, and obtain the negative electrode sheet;

[0045] After drying the negative electrode sheet, place it in water and soak it at 55°C for 6 hours, then continue to ultrasonicate it at the same temperature at a frequency of 100kHz for 2 hours to peel off the graphite negative electrode active material coating and the negative electrode current collector, remove the negative electrode current collector, collect the graphite negative electrode active material coating, dry it in an oven, and then crush the graphite negative electrode active material coating to obtain a crushed material;

[0046] Remove impurities:

[0047] The crushed material is transferred into a muffle furnace, and heat-treated at 400°C for 40 minutes in an air atmosphere, and then cooled, discharged, and calcined. The calcined material is then poured into a 15% sulfuric acid solution, and ultrasonically reacted for 3 hours at 75°C and an ultrasonic frequency of 80kHz. The filter cake is filtered, collected, and washed with deionized water until the washing solution is neutral, and dried to obtain a dry filter cake.

[0048] Then, the dried filter cake is ground and sieved to obtain a de-impurity material with a D50 of 12 μm, thereby obtaining a de-impurity material;

[0049] Shear Mixing:

[0050] The impurity-removing material and the polytetrafluoroethylene resin are mixed at a mass ratio of 15:1, and then 1.5% of the mass of the impurity-removing material is added with flaky nano-boehmite, and the mixture is continuously sheared and mixed for 3 hours at a temperature of 40° C. and a shear speed of 800 r / min to fiberize the polytetrafluoroethylene resin to obtain a precursor;

[0051] The D50 of the nano-boehmite is 150 nm;

[0052] High temperature carbonization:

[0053] The precursor was heated to 580°C at a rate of 0.3°C / min under inert gas protection, carbonized for 3 hours, and then cooled to room temperature with the furnace. After cooling, the material was discharged to obtain a carbonized material. The carbonized material was then mixed with a 6% sulfuric acid solution in a mass ratio of 1:8, and stirred for 2 hours at a stirring speed of 300r / min. The filter cake was then filtered, collected, and washed with deionized water until the washing liquid was neutral. The washed filter cake was then transferred to an oven for drying to obtain regenerated graphite.

[0054] Example 2

[0055] Stripping of graphite negative electrode:

[0056] Disassemble the lithium-ion battery, separate and remove the positive electrode sheet and the separator, and obtain the negative electrode sheet;

[0057] After drying the negative electrode sheet, place it in water and soak it at 65°C for 7 hours, then continue to ultrasonicate it at the same temperature for 3 hours at an ultrasonic frequency of 110kHz to peel off the graphite negative electrode active material coating and the negative electrode current collector in the negative electrode sheet, remove the negative electrode current collector, collect the graphite negative electrode active material coating, dry it in an oven, and then crush the graphite negative electrode active material coating to obtain a crushed material;

[0058] Remove impurities:

[0059] The crushed material is transferred into a muffle furnace, and heat-treated at 420°C for 50 minutes in an air atmosphere to remove the binder and the conductive agent, and then cooled, discharged, and calcined. The calcined material is then poured into a 15% sulfuric acid solution, and ultrasonically reacted for 3 hours at 75°C and an ultrasonic frequency of 80kHz. The filter cake is filtered, collected, and washed with deionized water until the washing solution is neutral, and dried to obtain a dry filter cake.

[0060] Then the dried filter cake is ground and sieved to obtain a de-impurity material with a D50 of 16 μm, thereby obtaining a de-impurity material;

[0061] Shear Mixing:

[0062] The impurity-removing material and polytetrafluoroethylene resin are mixed at a mass ratio of 18:1, and then 2% of the mass of the impurity-removing material is added with flaky nano-boehmite, and the mixture is continuously sheared and mixed for 4 hours at a temperature of 45° C. and a shear speed of 850 r / min to fiberize the polytetrafluoroethylene resin to obtain a precursor;

[0063] The D50 of the nano-boehmite is 160 nm;

[0064] High temperature carbonization:

[0065] The precursor was heated to 590°C at a rate of 0.4°C / min under inert gas protection, carbonized for 4.5 hours, and then cooled to room temperature with the furnace. After cooling, the material was discharged to obtain a carbonized material. The carbonized material was then mixed with a 7% sulfuric acid solution in a mass ratio of 1:9, and stirred for 2 hours at a stirring speed of 300r / min. The filter cake was then filtered and collected, and washed with deionized water until the washing liquid was neutral. The washed filter cake was then transferred to an oven for drying to obtain regenerated graphite.

[0066] Example 3

[0067] Stripping of graphite negative electrode:

[0068] Disassemble the lithium-ion battery, separate and remove the positive electrode sheet and the separator, and obtain the negative electrode sheet;

[0069] After drying the negative electrode sheet, place it in water and soak it at 75°C for 8 hours, then continue to ultrasonicate it at the same temperature at a frequency of 120kHz for 4 hours to peel off the graphite negative electrode active material coating and the negative electrode current collector in the negative electrode sheet, remove the negative electrode current collector, collect the graphite negative electrode active material coating, dry it in an oven, and then crush the graphite negative electrode active material coating to obtain a crushed material;

[0070] Remove impurities:

[0071] The calcined material was poured into a 15% sulfuric acid solution, and ultrasonically reacted for 3 hours at a temperature of 75°C and an ultrasonic frequency of 80kHz. The filter cake was collected by filtration, and washed with deionized water until the washing liquid was neutral, and dried to obtain a dry filter cake.

[0072] Then the dried filter cake is ground and sieved to obtain a de-impurity material with a D50 of 20 μm, thereby obtaining a de-impurity material;

[0073] Shear Mixing:

[0074] The impurity-removing material and polytetrafluoroethylene resin are mixed at a mass ratio of 20:1, and then 2.5% of the mass of the impurity-removing material is added with flaky nano-boehmite, and the mixture is continuously sheared and mixed for 5 hours at a temperature of 50° C. and a shear speed of 900 r / min to fiberize the polytetrafluoroethylene resin to obtain a precursor;

[0075] The D50 of the nano-boehmite is 180 nm;

[0076] High temperature carbonization:

[0077] The precursor is heated to 600°C at a rate of 0.5°C / min under inert gas protection, and carbonized for 6 hours. It is then cooled to room temperature with the furnace, and discharged after cooling to obtain a carbonized material. The carbonized material is then mixed with an 8% sulfuric acid solution in a mass ratio of 1:10, and stirred for 2 hours at a stirring speed of 300r / min. The filter cake is then filtered, collected, and washed with deionized water until the washing liquid is neutral. The washed filter cake is then transferred to an oven for drying to obtain regenerated graphite.

[0078] Example 4

[0079] The present embodiment differs from the embodiment 1 in that flaky alumina of the same mass and D50 is used to replace the flaky boehmite, and the other conditions remain unchanged.

[0080] Example 5

[0081] The present embodiment is different from the embodiment 1 in that spherical boehmite of equal mass and D50 is used to replace the flake boehmite, wherein the sphericity of the spherical boehmite is 8.6, and the other conditions remain unchanged.

[0082] Example 6

[0083] The present embodiment is different from the embodiment 1 in that the added amount of the flaky nano-boehmite is 1% of the mass of the impurity-removing material, and the other conditions remain unchanged.

[0084] Example 7

[0085] The present embodiment is different from the embodiment 1 in that the added amount of the flaky nano-boehmite is 2.8% of the mass of the impurity-removing material, and the other conditions remain unchanged.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is that PVDF of equal mass is used to replace the polytetrafluoroethylene resin, and other conditions remain unchanged.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is that no polytetrafluoroethylene resin is added, and other conditions remain unchanged.

[0090] The performance tests were performed on the products obtained in Examples 1-7 and Comparative Examples 1-2. The specific test methods and test results are as follows:

[0091] Cycle performance test:

[0092] The negative electrode active material, conductive carbon black Super-P and carboxymethyl cellulose were mixed in a mass ratio of 95:2:3, and deionized water was added as a solvent, and the mixture was stirred at a speed of 400 r / min for 8 hours to prepare a negative electrode slurry; then the negative electrode slurry was scraped on the surface of the copper foil, and dried at 100°C for 12 hours to obtain a negative electrode sheet, which was cut into a disc with a diameter of 12 mm, wherein the surface density of the active material on the surface of the negative electrode sheet was controlled at 2.7 mg / cm 2 ; In a glove box, a CR2032 battery shell was selected, a lithium sheet was used as a counter electrode and a reference electrode, and a porous polypropylene membrane (Clegard 2320) was used as a diaphragm. A button-type half-cell was assembled in the order of a negative electrode sheet, a diaphragm, an electrolyte, a lithium sheet, a gasket, and a shell, wherein the electrolyte was selected as a ternary mixture of 1 mol / L lithium hexafluorophosphate dissolved in ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 1:1:1; after the battery was assembled and sealed, it was allowed to stand at room temperature for 36 hours to perform electrochemical performance testing; a CT2001A blue electric test system was used with a test voltage range of 0.005-3.0V to perform a constant current charge and discharge test on the above battery, and after 500 cycles of continuous charge and discharge, the capacity retention rate of the battery corresponding to each embodiment or comparative example product was tested; the specific test results are shown in Table 1;

[0093] Gram capacity test of graphite negative electrode:

[0094] According to the above-mentioned formula of negative electrode sheet, the graphite negative electrode is made into a working electrode, assembled into a half-cell, and tested at a charge and discharge rate of 0.1C using an electrochemical workstation;

[0095] According to gram capacity = electric capacity (mAh) / mass of graphite negative electrode (g), gram capacity is calculated. The detailed calculation results are shown in Table 1;

[0096] Table 1: Product performance test results

[0097] Capacity retention rate / (%) Gram capacity / (mAh / g) Example 1 98.6 362.5 Example 2 98.5 363.1 Example 3 98.8 364.8 Example 4 96.2 355.7 Example 5 96.3 356.9 Example 6 97.3 347.1 Example 7 97.9 353.7 Comparative Example 1 94.8 339.9 Comparative Example 2 93.9 330.1

[0098] It can be seen from the test results in Table 1 that the product obtained by the present invention not only has a good capacity utilization, but also has a high capacity retention rate after long-term cyclic charge and discharge, and therefore has an excellent cycle life.

[0099] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for regenerating a graphite negative electrode of a lithium ion battery, characterized in that: The specific regeneration steps include: Stripping of graphite negative electrode: The graphite negative electrode active material coating is peeled off from the negative electrode current collector, and then the graphite negative electrode active material coating is crushed to obtain a crushed material; Remove impurities: The crushed material is heat treated in an air atmosphere at a temperature below 400°C, and then ultrasonically pickled to obtain a decontaminated material; Shear Mixing: The impurity-removing material and the polytetrafluoroethylene resin are mixed in a mass ratio of (15-20):1, and then sheared and mixed to fiberize the polytetrafluoroethylene resin to obtain a precursor; High temperature carbonization: The precursor is heated and carbonized under the protection of inert gas, and then sieved to obtain regenerated graphite.

2. A lithium ion battery graphite negative electrode regeneration method according to claim 1, characterized in that: The shear mixing comprises: The impurity-removing material and polytetrafluoroethylene resin are mixed in a mass ratio of (15-20):1, and then continuously shear-mixed for more than 3 hours at a temperature of 40-50°C to fiberize the polytetrafluoroethylene resin to obtain a precursor.

3. A lithium ion battery graphite negative electrode regeneration method according to claim 2, characterized in that: The shear mixing also includes: The impurity-removing material and polytetrafluoroethylene resin are mixed in a mass ratio of (15-20):1, and then 1.5-2.5% of the mass of the impurity-removing material is added with flaky nano-boehmite, and the mixture is continuously sheared and mixed for more than 3 hours at a temperature of 40-50° C. to fiberize the polytetrafluoroethylene resin to obtain a precursor.

4. A lithium ion battery graphite negative electrode regeneration method according to claim 3, characterized in that: The specific regeneration step also includes: Stripping of graphite negative electrode: The graphite negative electrode active material coating is peeled off from the negative electrode current collector, and then the graphite negative electrode active material coating is crushed to obtain a crushed material; Remove impurities: The crushed material is heat treated in an air atmosphere at a temperature below 400°C, and then ultrasonically pickled to obtain a decontaminated material; Shear Mixing: The impurity-removing material and polytetrafluoroethylene resin are mixed in a mass ratio of (15-20):1, and then 1.5-2.5% of the mass of the impurity-removing material is added with flaky nano-boehmite, and the mixture is continuously sheared and mixed for more than 3 hours at a temperature of 40-50° C. to fiberize the polytetrafluoroethylene resin to obtain a precursor; High temperature carbonization: The precursor is heated and carbonized under the protection of inert gas, and then discharged after cooling, and then acid-washed and dried to obtain regenerated graphite.

5. A lithium ion battery graphite negative electrode regeneration method according to claim 3, characterized in that: The impurity removal also includes: The crushed material is heat-treated in an air atmosphere to remove a binder and a conductive agent, and then ground and sieved to obtain a de-impurity material with a D50 of 12-20 μm; Furthermore, the D50 of the nano-boehmite is 150-180 nm.

6. A lithium ion battery graphite negative electrode regeneration method according to claim 1, characterized in that: The high temperature carbonization comprises: The precursor is heated to 580-600°C at a rate of 0.3-0.5°C / min under inert gas protection, carbonized for 3-6 hours, cooled to room temperature with the furnace, and discharged to obtain regenerated graphite.

7. A regenerated graphite, characterized in that: The lithium-ion battery graphite negative electrode is prepared by the regeneration method of the lithium-ion battery graphite negative electrode according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method of producing graphite fiber-reinforced fluororesin composites

    US5705120A

  • Electrochemical device and electronic device comprising same

    WO2021174443A1